Network Load Performance Monitoring pada Laboratorium Multimedia - Septiyani, Santi; Fatoni, Fatoni (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
The high network usage activity in the multimedia laboratory at Bina Darma University has the potential to create network load that impacts service quality. This study aims to monitor and analyze network performance using the Action Research method. Monitoring was conducted over six months, from June to November 2025, with observation frequency of five days a week on active laboratory days. Network performance evaluation used Quality of Service (QoS) parameters, including throughput, delay, jitter, and packet loss, based on TIPHON standards. Initial measurements showed an average throughput of 1.02 Mbps, delay of 39.18 ms, jitter of 44.57 ms, and packet loss of 2.64%, indicating that network performance was not yet optimal. During the monitoring period, fluctuations in QoS values were observed, particularly during peak activity, which resulted in increased delay and jitter. The research results indicate that the quality of network services tends to be unstable during certain periods, thus continuous monitoring and evaluation of the network are necessary.